A Review of Volume 5 of the Handbook of Regional and Urban Economics, Parts III and IV. (5th October 2017) - Davidoff, Thomas
Abstract: This paper reviews parts III and IV of the recent Handbook of Regional and Urban Economics. Many of the surveys within the Handbook relate to two phenomena of interest: the recent boom and bust cycle in U.S. housing markets, and the striking growth of home prices in a few global "Superstar Cities." Real Estate and Urban economists have made progress in modeling these phenomena. There is considerable room for future research, however. There is no coherent story explaining U.S. home price movements in the 2000s that does not run afoul of important stylized facts. We also have not yet identified the relative importance of supply constraints and demand growth in the rise of Superstar City prices.